2018
DOI: 10.1111/jvh.12936
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C among vulnerable populations: A seroprevalence study of homeless, people who inject drugs and prisoners in London

Abstract: Injecting drugs substantially increases the risk of hepatitis C virus (HCV) infection and is common in the homeless and prisoners. Capturing accurate data on disease prevalence within these groups is challenging but is essential to inform strategies to reduce HCV transmission. The aim of this study was to estimate the prevalence of HCV in these populations. We conducted a cross-sectional study between May 2011 and June 2013 in London and, using convenience sampling, recruited participants from hostels for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
(60 reference statements)
3
17
1
Order By: Relevance
“…Comparable to previous studies HCV RNA prevalence among the study population was high (23%), however, the majority of participants with HCV infection reported a history of injection drug use. Consistent with previous research, there was a strong relationship between reported HCV risk factors (history of injecting drug use or incarceration) and HCV RNA prevalence . In fact, the majority (n = 25, 63%) of those with HCV infection had a history of injecting and incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to previous studies HCV RNA prevalence among the study population was high (23%), however, the majority of participants with HCV infection reported a history of injection drug use. Consistent with previous research, there was a strong relationship between reported HCV risk factors (history of injecting drug use or incarceration) and HCV RNA prevalence . In fact, the majority (n = 25, 63%) of those with HCV infection had a history of injecting and incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the present study was to estimate the prevalence of HCV infection in the prison population in the greater Florianópolis area. Studies such as the present study may promote the improvement and development of strategies to reduce HCV transmission 3 .…”
mentioning
confidence: 82%
“…HCV outcomes are clearly influenced by other axes of inequality and characteristics of health systems, leading to syndemic interactions beyond that between HCV and HIV, for example, race/ethnicity and insurance status being associated with access to DAAs, marginalization of vulnerable populations (PWID, homeless persons, sex workers, etc.) with lower linkage‐to‐care figures, the current refugees crisis in the Mediterranean with high rates of undiagnosed HCV, or the opioid crisis in the USA with an increased number of acute HCV infections differently affecting PWID populations according to territory, age, gender, ethnicity or socioeconomic position . That is why we need to comprehensively study the social determinants of HCV epidemics globally and locally, design public policies, and integrated preventive strategies to approach them from the more structural causes of disease distribution to the more immediate risk factors, such as the sources of acquisition of HCV infection.…”
Section: Why We Need Daaswhy We Need Daasmentioning
confidence: 99%